Conflict and consensus in Switzerland - Schmid, Carol L. (University of California Press ; University of California Press, Ltd., 1981)
Schmid discusses this anomaly, concluding that Switzerland remains "united by a self-conscious political definition of nationhood", having developed a system early in its history that has ensured all ethnic and religious groups fair treatment politically, socially, and economically.